Self-reporting by older adults as victims of violence in Portugal: the remaining taboo issue - Gil, Ana Paula (2017)
This paper includes results from the qualitative methodologies on perceptions and meanings of violence in addition to prevalence data of violence experienced by individuals aged 60+ living in private households in Portugal. Findings from the help-seeking behaviour of the self-reported victims are also discussed. The combination of different methodologies in population based-prevalence studies is crucial for understanding the issue within society, namely how individuals apprehend the issue, the number of older adults that are potential victims and which types of institutions do they resort to when asking for help.